Development of a potential probiotic yoghurt using selected anti-inflammatory lactic acid bacteria for prevention of colitis and carcinogenesis in mice - del Carmen, Silvina Andrea (2016)
Aims: To evaluate the beneficial properties of a potentially probiotic yoghurt obtained by the fermentation of two selected anti-inflammatory bacterial strains using in vivo mouse models of intestinal inflammation and colon carcinogenesis. Methods and Results: Yoghurt was administered to mice suffering chemically induced intestinal inflammation or colon carcinogenesis. It was shown that this novel yoghurt was able to prevent local inflammation in the intestines of mice through a regulation of the immune response, prevent macroscopic and histological damages, and prevent colon carcinogenesis through an anti-inflammatory response. Conclusions: The developed yoghurt showed in vivo anti-inflammatory properties by modulation of the host immune response for the prevention of colon inflammation and carcinogenesis. Significance and Impact of the Study: This new yoghurt could thus be considered a probiotic food and be useful as a complement to current treatment protocols for inflammatory bowel diseases and colon cancer, a first since there are no current functional foods specifically oriented for these patients.